The analysis of Angiotensin-I Converting Enzyme (ACE) by maitake (Grifrola frondosa) mycelia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
The Maitake (Grifola frondosa) is useful in treating diseases, specifically hypertension. Research on the maitake mycelia’s biological properties, nevertheless, are limited in the literature. This study aimed to (i) produce mushroom biomass adopting submerged fermentation, and (ii) investigate the Angiotensin-I Converting Enzyme inhibitory activity. Maitake mycelia’s yield after 14 days of fermentation under controlled conditions (approx. 1.32 g/L) were freeze-dried into powder and later were hydrolysed for analyses of Angiotensin-I Converting Enzyme inhibitory activity. Current results showed that the degree of hydrolysis increased in line with hydrolysis time, as the protein concentration for hydrolysed sample was 283.61 ± 7.14 µg/mL, however, the non-hydrolysed sample resulted in lesser protein content (46.76 ± 1.09 µg/mL). The hydrolysate maitake mycelia has higher Angiotensin-I Converting Enzyme inhibitory activity (46.48%) as compared to the non-hydrolysate maitake mycelia (20.19 ± 0.17%). This finding suggested maitake mycelia hydrolysate can be a source of potential bioactive peptides used in treating hypertension.
Keywords: maitake mycelia; mushroom; protein; hydrolysis; fermentation